Insights into the impurities of Bi2WO6 synthesized using the hydrothermal method. Issue 67 (9th November 2020) - Liu, Jiayou; Nie, Qianqian; Tan, Zhongchao; Luo, Yulin; Wang, Shuai; Yu, Hesheng
Abstract : Impurities of Bi2 WO6 formed during the hydrothermal process under a wide range of acid–base conditions (from 1.5 M HNO3 to 0.5 M NaOH) were qualitatively analyzed and accurately quantified for the first time. Abstract : Bismuth tungstate (Bi2 WO6 ) nanomaterials are widely used as visible-light driven photocatalysts. However, limited attention has been paid to the purity of prepared Bi2 WO6 nanoparticles, which may affect the photocatalytic performance and hinder in-depth study of Bi2 WO6 . In this work, the impurities of Bi2 WO6 formed during the hydrothermal process under a wide range of acid–base conditions (from 1.5 M HNO3 to 0.5 M NaOH) were qualitatively analyzed and accurately quantified for the first time. After confirmation of Bi2 WO6 stability, the impurities were dissolved using acid or base treatment, followed by measurements of the ion concentrations using Inductively Coupled Plasma Mass Spectrometry (ICP-MS). Furthermore, various characterization techniques including XRD, FE-SEM, TEM, UV-Vis DRS, XPS and FTIR were implemented to explore the change in morphology and optical properties of Bi2 WO6 prepared in different acid–base environments, and to facilitate qualitative analysis of impurities. The hydrolytic properties of raw materials used for the synthesis of Bi2 WO6 were also analyzed with UV-Vis transmittance observation. Following these analyses, the types and contents of impurities in Bi2 WO6 prepared by the hydrothermal method under different acid–base conditions were determined. Results show that the primary impurity is WO3 ·0.33H2 O (41.09%) for the precursor prepared in 1.5 M nitric acid solution. When the pH of the precursor was in the range of 0.97–7.01, the synthesized Bi2 WO6 has relatively high purity, and the impure products were identified as BiONO3 . Bi2 O3 began to appear when pH reached 9.01 and it reached 18.88% when pH was 12.98. The final product was Bi2 O3 exclusively for the precursor conditioned in 0.5 M NaOH solution. In addition, the accuracy of the proposed quantitative method using ICP-MS was validated for several scenarios by weight difference experiments.